ETIKA GURU DALAM PERSPEKTIF IMAM AL-GHAZALI - Damanhuri (AS-SALAM, 2013)
Al-Ghazali owned the big contribution in order to develop good educator profile and as according to syari'at Islam. This Matter was seen from How Imam al-Ghazali gave the congeniality, condition, civil obligation and duty which was in line with demand or Islam teaching, both for educator.        So that operationally, its concept can be applicated and made as a reference alternative for a educator now, especially in scope of Islam education itself, but has to use the new approach form and also needed a completion which is in line with the growth and epoch progress.